Raw Materials, Profits, and the Productivity Slowdown - Bruno, Michael (Quarterly Journal of Economics, 1984)
A factor-price frontier framework is used to clarify the analogy of an increase (decrease) in raw material prices with autonomous technological regress (progress). Factor-price profiles are estimated for the manufacturing sector of the United States, the United Kingdom, Germany, and Japan. The production model, in conjunction with estimates obtained from the factor-price frontier, attributes much of the slowdown in manufacturing productivity to the rise in relative raw material prices. Part of the apparent productivity riddle may have to do with the use of double-deflated national accounting measures of value added, which have an inherent measurement bias.